2006
DOI: 10.1590/s0100-204x2006001200011
|View full text |Cite
|
Sign up to set email alerts
|

Ácidos graxos da gema e composição do ovo de poedeiras alimentadas com rações com farelo de coco

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da inclusão do farelo de coco (FC) na ração e do tempo de alimentação de poedeiras comerciais, sobre os ácidos graxos da gema e os componentes do ovo. O delineamento foi em esquema fatorial 5x2, com cinco níveis de inclusão do FC (0, 5, 10, 15 e 20%) e dois tempos de alimentação (14 e 28 dias). Foram avaliados o peso e as porcentagens de albúmen, gema e casca dos ovos, bem como os sólidos e lipídios totais e o perfil de ácidos graxos das gemas. A inclusão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
3
0
5
Order By: Relevance
“…The lipid profile of the egg yolk is influenced by genetics, egg size, feed composition, and type of fat added to feed (Barreto et al, 2006;Cherian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid profile of the egg yolk is influenced by genetics, egg size, feed composition, and type of fat added to feed (Barreto et al, 2006;Cherian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da grande demanda por pesquisas com fontes alternativas, a utilização de ingredientes não convencionais em rações de poedeiras apresenta limitação (BARRETO et al, 2006), uma vez que o valor nutricional do ovo pode sofrer alterações indesejáveis.…”
Section: Introductionunclassified
“…Barreto et al (2006) also did not observed differences in yolk moisture and total solids content when hens were fed diets containing up to 20% of coconut meal. According to Ahn, Kim All injections were made in a split less mode.…”
Section: Moisture Total Solids and Total Lipids Of The Yolkmentioning
confidence: 64%
“…According to Barreto et al (2006), the yolk lipid content may be influenced by strain, egg size, and diet components, as well as by the type of fat in the diet. Total lipid content found in the yolks in this study is lower than that reported by Fennema (2000), who found values ranging from 32 to 35%.…”
Section: Egg Quality Characteristicsmentioning
confidence: 99%